Electroacupuncture at ST36 Protects ICC Networks via mSCF/Kit-ETV1 Signaling in the Stomach of Diabetic Mice. (22nd January 2017) - Tian, Lugao; Zhu, Beibei; Liu, Shi
Abstract : Background . Electroacupuncture (EA) at ST36 has been used to regulate gastric motility and effectively improve gastric emptying in diabetic patients. Nevertheless, the specific mechanisms underlying the efficacy of this treatment remain unknown. The aim of this study was to assess the variations of interstitial cells of Cajal (ICC) and explore the changes in mSCF/KIT-ETV1 signaling in the antrum and corpus of diabetic mice after treatment with EA. Methods . Male C57BL/6 mice were randomized into five groups: control group, diabetic group (DM), diabetic-plus-sham EA group (SEA), diabetic-plus-low-frequency EA group (LEA), and diabetic-plus-high-frequency EA group (HEA). The expression levels of Ano1, c-Kit, and ETV1 were assessed by immunofluorescence in the antrum and corpus. Western blotting and PCR methods were further used to evaluate c-Kit, mSCF, and ETV1 expression. Results . (1) c-Kit and Ano1 were obviously decreased in the DM group, but c-Kit reduced much more than Ano1. (2) The mSCF, c-Kit, and ETV1 mRNA and protein levels were obviously decreased in the DM group in both the antrum and the corpus (P < 0.01 ), but they were significantly elevated in the LEA and HEA groups (P < 0 . 01 ). Conclusions . Ano1 is a reliable marker to detect ICC changes in diabetes; low- and high-frequency EA at acupoint ST36 can protect the networks of ICC possibly via normal activation of mSCF/KIT-ETV1 signaling.